Sdom pa gsum gyi rab tu dbye baʼi gźuṅ lugs legs par bśad pa : a detailed commentary on Sa-skya Paṇḍi-taʼs famed Sdom gsum rab dbye - Rin-chen-rgyal-mtshan, Spos-khaṅ-pa, 15th cent (Trayang and Jamyang Samten, 1977)
Commentary on the Sdom gsum rab dbye of Sa-skya Paṇḍi-ta Kun-dga'-rgyal-mtshan, 1182-1251, verse treatise on the concept of the three disciplines or vows (samaya) in Buddhism.